The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3122/jabfm.2013.06.120248
|View full text |Cite
|
Sign up to set email alerts
|

Management of Early Pregnancy Failure and Induced Abortion by Family Medicine Educators

Abstract: Background: Reproductive health care, including treatment of early pregnancy failure (EPF) and induced abortion, is an integral part of patient-centered care provided by family physicians, but data suggest that comprehensive training is not widely available to family medicine residents. The purpose of this study was to assess EPF and induced abortion management practices and attitudes of family medicine physician educators throughout the United States and Canada.Methods: These data were collected as part of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
(15 reference statements)
1
10
0
1
Order By: Relevance
“…Spontaneous abortion occurs unintentionally, due to factors such as sexually transmitted diseases (including syphilis, gonorrhea, chlamydia, and trichomonas vaginalis), occupation, environmental factors (chemicals, metals, tobacco smoking, alcohol consumption, night work and so on) acute anemia, or accidents (such as falling down) . However, induced abortion is performed due to provocation from the outside by intentionally terminating an unwanted pregnancy …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous abortion occurs unintentionally, due to factors such as sexually transmitted diseases (including syphilis, gonorrhea, chlamydia, and trichomonas vaginalis), occupation, environmental factors (chemicals, metals, tobacco smoking, alcohol consumption, night work and so on) acute anemia, or accidents (such as falling down) . However, induced abortion is performed due to provocation from the outside by intentionally terminating an unwanted pregnancy …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] However, induced abortion is performed due to provocation from the outside by intentionally terminating an unwanted pregnancy. 5,6 Although induced abortion has been used as a family planning method for many years, it is an important problem in women's health, especially in developing countries and especially in rural areas where the procedure is often unsafe, due to poor medical conditions. Unsafe induced abortion can have dire consequences for women, their families and society as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…While these findings seem to support abortion provision in the primary care setting, only 15.3% of survey respondents were offering early abortion care. 8 This discrepancy is partially explained by the fact that only 7% of family medicine residency programs include routine training in early abortion care. 9 Several studies have demonstrated how particular aspects of receiving abortion care within the primary care setting are acceptable to patients, and, in some cases, preferable.…”
Section: Original Articlesmentioning
confidence: 99%
“…Kupetsky et al 16 provide a useful review of diagnosing and treating psoriasis for primary care clinicians. Wahlert 19 revealed that most academic family physicians have experience treating failure of early pregnancy, often with medications, but a minority have provided abortions during early pregnancy.…”
Section: Care Of Patients With Specific Health Issuesmentioning
confidence: 99%